The place for DIY cultures and the territories of cinema and audio-visual in Portugal: challenges and perspectives - Costa, P.; Lopes, R., V.; Tomaz, E.; Almeida, Rodrigo Nicolau (KISMIF CONFERENCE 2022 “Keep It Simple, Make It Fast!” – “DIY CULTURES, SUSTAINABILITY AND ARTISTIC ECOSYSTEMS”, 2022)
This presentation aims to discuss the place and the development prospects for DIY cultures within the cinema-audiovisual sector in Portugal, addressing address the main challenges to the sustainability of their dynamics. On the one hand, the development of DIY dynamics in the sector in Portugal is problematized in the light of the technological, economic, social and cultural transformations that are affecting the sector, as well as its place in the context of national creative milieus/ecosystems. On the other hand, the potential for their development is considered in the light of the geographical asymmetries and the extreme spatial concentration observed in the field of film creation and production in Portugal, as well as considering the territoriality inherent to these dynamics and to the development of consistent and sustainable creative milieus. The work is based on a comprehensive diagnosis of the reality of the sector, prepared by the authors as part of a research project carried out for ICA – Portuguese Institute of Cinema and Audiovisual - during 2021. In addition to documental and legislative analysis, this study was supported in an in-depth analysis of the available statistical data on the sector and on an extensive database of interviews and focus groups to key agents, through which more than 70 individuals representing the diversity of the field were heard. The main critical points and challenges that arise concerning this topic in Portugal are systematized and it is mapped a set of fields which are identified as central for public action in this area.